Comparison Analysis of the Port Business Between PT. Pelabuhan Indonesia (Persero) and PSA International Singapore - Syifa Fajar Maulani; Ira Nirmala; Muhammad Rizky; Maskur Faris Ardani; Melia Handayani; Muhammad Alfalah (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
Maritime transportation, as a key element of global trade, offers significant economic advantages, with ports playing a crucial role in ensuring the smooth flow of goods. The increasing number of ship visits highlights the need for port infrastructure development to improve operational efficiency. This study aims to compare the port business between PT. Pelabuhan Indonesia (Persero) and PSA International in Singapore. The research employs a qualitative method, using the Business Model Canvas (BMC), PESTEL analysis, and gap analysis to compare key elements in both ports. The findings reveal significant differences in technology and infrastructure between Pelindo and PSA. PSA excels in the application of advanced technology, while Pelindo focuses more on domestic infrastructure development. These recommendations are expected to provide insights for Pelindo to improve its business processes and competitiveness in the international market, as well as to support the achievement of the Sustainable Development Goals (SDGs), specifically Goal 9.